Diseño del chasis de un vehículo eléctrico autónomo para la ciudad de Cartagena de Indias (SETA-tren del Caribe) usando elementos finitos y la técnica de Shell (2020)
This document contains the chassis design for an autonomous electric vehicle. First, a fatigue failure analysis should be done to the underside of the chassis under fluctuating loads. Subsequently, the methodology of the shell technique or plate technique is applied to make the structural analysis by finite elements of the complete structure. The results show a satisfactory design that meets all the criteria used.